Odpowiedź :
a)
[tex] \frac{1}{3} x + 4 = \frac{1}{2} x + 5 | \times 6 \\ 2x + 24 = 3x + 30 \\ - x = 6 \\ x = - 6[/tex]
b)
[tex] \frac{x - 2}{7} = \frac{x + 4}{10} \\ 10(x - 2) = 7(x + 4) \\ 10x - 20 = 7x + 28 \\ 3x = 48 \\ x = 16[/tex]
Odpowiedź:
a) [tex]\frac{1}{3} x + 4 = \frac{1}{2} x + 5[/tex]
1/3x + 4 = 1/2x + 5 | - 1/3x
4 = 1/2x - 1/3x + 5 | -5
-1 = 3/6x - 2/6x
-1 = 1/6x | * 6
-6 = x
b ) [tex]\frac{x - 2}{7} = \frac{x + 4}{10}[/tex]
x-2 / 7 = x+4 / 10
1/7x - 2/7 = 1/10x + 4/10 | * 7
x - 2 = 7/10x + 28/10 | * 10
10x - 20 = 7x + 28 | -7x
3x - 20 = 28 | +20
3x = 48 | : 3
x = 16